Early larval development of the rock shrimps Sicyonia dorsalis Kingsley, 1878 and S. typica (Boeck, 1864) (Dendrobranchiata) with remarks of larval morphology of Sicyoniidae Ortmann, 1898 - Pantaleão, João Alberto Farinelli [UNESP]; Pescinelli, Régis Augusto [UNESP]; Mantelatto, Fernando Luis; Costa, Rogério Caetano [UNESP] (FapUNIFESP (SciELO), 2022)
The aim of this study was to describe and illustrate the early larval stages, i.e., the complete naupliar development and the first protozoea (PZI) of Sicyonia dorsalis and S. typica obtained under laboratory conditions. We also provide remarks from a comparative analysis of the morphology of these stages among representatives of the genus and furnish morphological characteristics to distinguish them from another penaeoidean in the plankton. Our results indicate that the naupliar development of Sicyonia is composed of five stages (NI to NV). No differences were found in the morphology of the naupliar and PZI stages of the two studied species, even though they are considered phylogenetically distant into the genus. We suspect that morphological differences arise later during ontogenetic development. The comparisons with larval descriptions of congeners revealed that naupliar stages and PZI were very similar, nevertheless, some morphological differences were observed. As illustrated here, there is a clear need of new descriptions of the studied group and generalizations and conclusions of larval morphology patterns at this point need to be made with caution, because data of a still insufficient number of species is available.
Desenvolvimento larval inicial dos camarões-pedra Sicyonia dorsalis Kingsley, 1878 e S. typica (Boeck, 1864) (Dendrobranchiata) com observações sobre a morfologia larval de Sicyoniidae Ortmann, 1898
Keywords: Decapoda; larval morphology; metanauplius; nauplius; Penaeoidea; protozoea